Mechanism of destruction of erythrocytes. Intravascular hemolysis - Cuadra, Manuel (1957)
It has made the study of the mechanism of destruction of erythrocytes from a new perspective: through research stroma in wet mounts (dark field) and blood smears stained with an original method.